2021
DOI: 10.3390/pr9081459
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Remaining Useful Life of Proton Exchange Membrane Fuel Cells under Variable Loading Conditions Online

Abstract: The major challenges for the commercialization of proton exchange membrane fuel cells (PEMFCs) are durability and cost. Prognostics and health management technology enable appropriate decisions and maintenance measures by estimating the current state of health and predicting the degradation trend, which can help extend the life and reduce the maintenance costs of PEMFCs. This paper proposes an online model-based prognostics method to estimate the degradation trend and the remaining useful life of PEMFCs. A non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Second, other criteria, such as the fitness improvement rate and population diversity, should be considered by MSPSOTLP during the solution update process to preserve the novel particles that can bring long-term success for the algorithm. Finally, it is worth it to investigate the feasibility of ANN optimized by MSPSOTLP to address challenging issues encountered in the intelligent condition monitoring of complex industrial systems [2], such as the remaining useful life prediction of gear pumps [72], the time series prognosis of fuel cells [73], and predictive maintenance of renewable energy systems [74].…”
Section: Discussionmentioning
confidence: 99%
“…Second, other criteria, such as the fitness improvement rate and population diversity, should be considered by MSPSOTLP during the solution update process to preserve the novel particles that can bring long-term success for the algorithm. Finally, it is worth it to investigate the feasibility of ANN optimized by MSPSOTLP to address challenging issues encountered in the intelligent condition monitoring of complex industrial systems [2], such as the remaining useful life prediction of gear pumps [72], the time series prognosis of fuel cells [73], and predictive maintenance of renewable energy systems [74].…”
Section: Discussionmentioning
confidence: 99%
“…Ao et al [15] proposed an RUL prediction method based on the Kalman filter in the frequency domain to process aging data of PEMFC in groups. Wang et al [16] established an aging model based on polarization curves, used the particle filter algorithm to estimate the aging parameters online, and used the rated voltage as a new health index. Although model-based methods can analyze the aging process combined with the mechanism, the aging mechanism of PEMFC has not been thoroughly studied, and various aging models are usually unproven, so the prediction accuracy of model-driven methods is usually not guaranteed [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experiment showed that the technique could accurately forecast the degeneration trend of the PEMFC output tension and aging parameters under different training stages. Focusing on the difficulties in online predictions, Penghao Wang [87] and other scholars proposed a nonlinear empirical degradation model and then employed PF to estimate the degradation state variables online to achieve the online prediction standard of the PEMFC. Taking the rated voltage as the new aging index, it could achieve superb life predictions in variable load and online predictions.…”
Section: Hybrid Approachesmentioning
confidence: 99%